Efficacy and safety of rush immunotherapy with alumprecipitated allergens in canine atopic dermatitis - Hobi, S.; Mueller, Ralf S. (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2014)
Objectives: Canine atopic dermatitis is a very common disease in small animal practice. Its only specific treatment is allergen immunotherapy. In rush-immunotherapy (RIT) increasing doses of allergen extract are injected subcutaneously in short intervals. Maintenance doses are achieved within one day compared to weeks or months with conventional immunotherapy. The aim of this study was to evaluate the safety and efficacy of RIT with alum-precipitated allergens. Materials and methods: A series of 20 dogs with atopic dermatitis underwent RIT with alum-precipitated allergens. Pruritus and medications at the start of the immunotherapy and 12 months afterwards were compared and adverse effects were recorded. Results: Significant improvement in pruritus (p = 0.0001) and medication scores (p = 0.0004) was noted after approximately 12 months of treatment. The observed clinical response was good to excellent in 70% of the dogs, consistent with other published reports. One dog vomited once during the induction day, with no other clinical problems and completion of the normal protocol. The other 19 dogs showed no adverse effects at all during or after RIT. Conclusion and clinical relevance: RIT with alum-precipitated allergens seems to be a safe and efficacious method to treat dogs with atopic dermatitis.
Keywords: Dog; allergy; desensitization; treatment